Dietary Iron Deficiency and Oversupplementation Increase Intestinal Permeability, Ion Transport, and Inflammation in Pigs. Issue 8 (29th June 2016) - Li, Yihang; Hansen, Stephanie L; Borst, Luke B; Spears, Jerry W; Moeser, Adam J
Abstract: Background: Understanding the influence of dietary iron deficiency and dietary iron oversupplementation on intestinal health is important for both animal production and human health. Objective: The aim of this study was to determine whether dietary iron concentration influences intestinal physiology, morphology, and inflammation in the porcine duodenum. Methods: Twenty-four male pigs (21 d old) were fed diets containing either 20 mg Fe/kg [low dietary iron (L-Fe)], 120 mg Fe/kg [adequate dietary iron (A-Fe); control], or 520 mg Fe/kg [high dietary iron (H-Fe)] by FeSO4 supplement (dry matter basis). After 32–36 d, the duodenum was harvested from pigs and mounted in Ussing chambers for the measurement of transepithelial electrical resistance (TER), short-circuit current, and 3 H-mannitol permeability. Intestinal morphology and inflammation were assessed by histologic examination, and proinflammatory gene expression was assessed by real-time polymerase chain reaction. Results: Compared with A-Fe–fed pigs, pigs fed L-Fe diets exhibited reduced TER (by 30%; P < 0.05). Compared with that of A-Fe–fed controls, the paracellular flux of 3 H-mannitol across the duodenal mucosa was higher ( P < 0.05) in L-Fe–fed (>100%) and H-Fe–fed (∼4-fold) pigs; the L-Fe–fed and H-Fe–fed groups did not differ significantly from one another. Compared with the L-Fe–fed pigs, the A-Fe–fed and H-Fe–fed pigs had malondialdehyde concentrations 1.4- and 2.5-fold higher in the duodenum and 4.4- and 6.6-fold higher in the liver, respectively ( P < 0.05). Neutrophil counts were higher in both the L-Fe–fed (by 3-fold) and H-Fe–fed (by 3.3-fold) groups than in the A-Fe–fed group; the L-Fe–fed and H-Fe–fed groups did not significantly differ from one another. Duodenal mucosal tumor necrosis factor α ( TNFA ), interleukin ( IL ) 1β, and IL6 relative gene expression was upregulated by 36%, 28%, and 45%, respectively, in H-Fe pigs ( P < 0.05), but not in L-Fe pigs, compared with A-Fe pigs. Conclusion: These data suggest that adequate but not oversupplementation of dietary iron in pigs is required to maintain intestinal barrier health and function.